2021
DOI: 10.3389/fpsyt.2021.716593
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelic-Assisted Psychotherapy After COVID-19: The Therapeutic Uses of Psilocybin and MDMA for Pandemic-Related Mental Health Problems

Abstract: The COVID-19 pandemic stands to have impacts on mental health and well-being that will extend beyond its formal resolution. Before COVID-19, mental health disorders were already challenging global healthcare systems, directly accounting for 7.4% of the total burden of disease (1, 2). An estimated 1 billion people worldwide suffer from a mental health disorder, with the two most common disorders-depression and anxiety-costing the global economy US$1 trillion per year (3). Stigma and limited treatment options ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…A recent review has suggested that psychedelics could be an effective treatment option for the mental health sequelae of COVID‐19 3 . Psychedelics have been traditionally used in spiritual and religious practices, but in recent years, there has been a resurgence of research on the therapeutic potential of psychedelics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review has suggested that psychedelics could be an effective treatment option for the mental health sequelae of COVID‐19 3 . Psychedelics have been traditionally used in spiritual and religious practices, but in recent years, there has been a resurgence of research on the therapeutic potential of psychedelics.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has suggested that psilocybin and 3,4‐methylenedioxymethamphetamine (MDMA) may be an effective treatment option for the mental health challenges associated with COVID‐19. 3 Psychedelics have been traditionally used in spiritual and religious practices, but in recent years, there has been a resurgence of research on the therapeutic potential of psychedelics. 4 Psychedelics have shown promise in the treatment of various medical conditions such as depression, anxiety, PTSD, and addiction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review has suggested that psilocybin and 3,4-Methylenedioxymethamphetamine (MDMA) may be an effective treatment option for the mental health challenges associated with COVID. 3 Psychedelics have been traditionally used in spiritual and religious practices, but in recent years, there has been a resurgence of research on the therapeutic potential of psychedelics. 4 Psychedelics have shown promise in the treatment of various medical conditions such as depression, anxiety, PTSD, and addiction.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, psilocybin drugs have been tested against COVID-19 for mental health problems caused by the pandemic, and the results of the clinical trials indicate that psychedelics are physiologically and psychologically safe (19). Psilocybin has been reported to be effective in treating depression recently (20).…”
Section: Introductionmentioning
confidence: 99%